Residual life of a historic riveted steel bridge - engineering critical assessment approach - Dorin Radu; Radu Băncilă; Simon Sedmak; Mihajlo Aranđelović (Elsevier - Procedia Structural Intergrity, 2022)
Sustainability has become an increasingly important component of requirements for the rehabilitation of bridge structures. Responsible use of our limited natural resources is essential for future generations, so the whole bridge rehabilitation process must be taken into account, in terms of structural integrity. The environmental impact for these types of structures is major – demolition and reconsideration of e.g. reinforced concrete structure being examples of poor management of resources and energy. On the existing roads and railways network steel bridges with more than 100 years in service lifetime are numerous. The in-service safety assessment of these structures is a complex problem. This article emphasizes the importance of rehabilitating the structure of existing steel bridges, considering the historical monument character of these structures, as well as the reuse of existing structures, part of sustainable development. The paper is presenting a study case for an historical riveted steel bridge build in the beginning of twentieth century, with an assessment method considering the structural integrity by means of fracture mechanics.
Keywords: historical steel bridges; fracture mechanics; structural integrity